SERVANT LEADERSHIP - Manalullaili Manalullaili (Wardah, 2014)
"Servant leadership" is one form of leadership style that is based sincerity and provide help without thought of personal gain or reward to be gained. Servant leadership is different with transformational leadership and transactional leadership. Because this type of leadership is a combination of environmental assessment related to good behaviour "akhlakul karimah". Greenleef are researchers who agree that this leadership style is very "up to date" and can apply to any form of organization, including educational organizations. This paper will explain what it is "servant leadership", the characteristics of which can be categorized as "servant leadership", advantages and disadvantages, and how to apply them into educational organizations, for example: UIN Raden Fatah Palembang